PENERAPAN TARGET COSTING DALAM UPAYA MENINGKATKAN EFISISENSI BIAYA PRODUKSI - Manalu, Elita Tia Monica; Hia, Resi Restu; Saribu, Ardin Dolok; Zega, Nopitri; Sijabat, Juni Debora; Nainggolan, Jestri Sumerdi; Simatupang, Mula (Jurnal Akuntansi Kompetif, 2025)
The main objective of this critical journal is to analyze the advantages and disadvantages of the main journal articles in the application of target costing in an effort to improve production cost efficiency. This study uses a target costing approach which is expected to be an effective production cost control tool. The research method used is the literature study method. The main journal used is "TARGET COSTING: EXPLORING THE CONCEPT AND ITS RELATION TO COMPETITIVENESS" and several other national comparative journals. The results of the study revealed that the Implementation of Target Costing is a crucial strategy in improving the efficiency of the company's production costs amidst increasingly tight market competition, Target Costing allows companies to be more adaptive to changes in consumer needs and tastes. Strategically, Target Costing not only functions as a cost control tool, but also as a managerial approach that is integrated with long-term planning, Target Costing not only functions as a cost control tool, but also as a managerial approach that is integrated with long-term planning. Keywords: Target costing, Efficiency, Production costs, Competitiveness, Cost control